Bubble Test and Carotid Ultrasound to Guide Indication of Transesophageal Echocardiography in Young Patients With Stroke - Mayerhofer, Ernst; Kanz, Dirk; Guschlbauer, Brigitte; Anderson, Christopher D.; Asmussen, Alexander; Grundmann, Sebastian; Strecker, Christoph; Harloff, Andreas (Frontiers in Neurology, 2022)
Background and Purpose: Indication of transesophageal echocardiography (TEE) in patients <=60 years with brain ischemia is uncertain. Methods: This prospective double-blinded study included patients with cryptogenic acute ischemic stroke or TIA >18 and <=60 years. After routine diagnostics, all patients underwent patent foramen ovale (PFO) screening by transcranial Doppler bubble test, carotid ultrasound for atherosclerosis screening (intima-media-thickness >0.90 mm or plaques), and TEE. We calculated sensitivity, specificity, PPV, and NPV of the combined non-invasive ultrasound to predict therapy-relevant TEE findings. Results: We included 240 consecutive patients (median 51 years, 39% female) of which 68 (28.3%) had both a negative bubble test and no carotid atherosclerosis. Of these, 66 (97.1%) had unremarkable TEE findings; in one patient a small PFO was found and closed subsequently, in another patient a 4.9 mm thick aortic atheroma was found, and double platelet inhibition initiated. Of the other 172 (71.7%) patients, 93 (54%) had PFO and 9 (5.2%) complex aortic plaques. No other therapy-relevant findings were present in both groups. Non-invasive ultrasound had a sensitivity of 98.0%, specificity of 47.8%, NPV of 97.1%, and PPV of 58.1% for therapy-relevant TEE findings. Conclusions: Bubble test and carotid ultrasound could be used for the individual decision for/against TEE in cryptogenic stroke patients <=60 years. If they are unremarkable TEE can be omitted with high safety regarding secondary prevention. If bubble test is positive and/or carotid ultrasound shows atherosclerosis, TEE should be carried out if PFO or aortic atheroma are potentially relevant for further patient management.